2018
DOI: 10.1002/cplu.201800247
|View full text |Cite
|
Sign up to set email alerts
|

Benzoylguanidines as Anion‐Responsive Systems

Abstract: A series of benzoylguanidinium salts was prepared and the changes in UV/Vis spectra, triggered by the presence of anions, were investigated. All compounds undergo deprotonation with basic anions like dihydrogenphosphate and acetate in acetonitrile. The most pronounced spectral changes were obtained by deprotonation of N1‐benzoyl‐N3‐(p‐nitrophenyl) guanidinium chloride which shows the naked‐eye visible color change from colorless to yellow. Measured pKa(BH+) in acetonitrile ranges from 12–16, which is comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…We designed GADAC to have a preorganized structure that presents four hydrogen bond donating groups to an oxoaniontwo from a guanidinium group, one from a carbazole N–H, and one from a 2-aminopyridine N–H (Scheme ). An intramolecular hydrogen bond between the guanidinium group and a second pyridino nitrogen is intended to restrict aryl C–N bond rotation and maintain planarity. The two pyridino groups are intended to lower the p K a values of the guanidinium and amino groups and, thereby, enhance their ability to donate hydrogen bonds to oxoanions. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We designed GADAC to have a preorganized structure that presents four hydrogen bond donating groups to an oxoaniontwo from a guanidinium group, one from a carbazole N–H, and one from a 2-aminopyridine N–H (Scheme ). An intramolecular hydrogen bond between the guanidinium group and a second pyridino nitrogen is intended to restrict aryl C–N bond rotation and maintain planarity. The two pyridino groups are intended to lower the p K a values of the guanidinium and amino groups and, thereby, enhance their ability to donate hydrogen bonds to oxoanions. …”
Section: Resultsmentioning
confidence: 99%
“…5−12 For example, the installation of an adjacent amide or pyrrole moiety can increase the affinity of a guanidinium-containing compound for oxoanions. 15,16 Likewise, decreasing the pK a value of a guanidino group can enhance affinity 17 because hydrogen bond donors and acceptors with more closely matched pK a values form stronger hydrogen bonds. 18−20 In that regard, a common strategy has been to employ an N-acylguanidinium group, which has a pK a of 8.3 compared to that of 13.7 for an N-alkylguanidinium group.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also checked whether the change in long range correction parameters (ω‐values) will additionally improve the simulated spectra. Namely, it has been shown that for some systems calculations with an “optimized” ω‐value give better agreement of the calculated spectra than the default one . For this purpose, we used ω‐values of 0.20, 0.15 and 0.10 |a 0 –1 |.…”
Section: Resultsmentioning
confidence: 99%
“…Guanidines are organic compounds that possess very interesting physico-chemical properties, such as very high basicity [1,2] and biological activity [3]. Their chemical behavior is extensively studied and guanidines have found applications in various fields, such as catalysis [4], coordination chemistry [5], supramolecular chemistry [6], medicinal chemistry [7,8] and chemical sensoring [9,10]. Whereas this versatile functional group undergoes numerous chemical reactions, guanidines are rarely involved in cycloaddition reactions [11], either in Diels-Alder or dipolar cycloadditions.…”
Section: Introductionmentioning
confidence: 99%